Learning losses and educational inequalities in Europe: Mapping the potential consequences of the COVID-19 crisis - Blaskó, Zsuzsa; Costa, Patricia da; Schnepf, Sylke V (Journal of European social policy, 2022)
It is widely discussed that the pandemic has impacted educational inequalities across the world. However, in contrast to data on health or unemployment, data on education outcomes are not timely. Hence, we have extremely limited knowledge about pandemic-related learning losses at the national and cross-national levels. As it might take years to get suitable comparative data, this study uses the latest large-scale international achievement survey from before the pandemic, the Trends in International Mathematics and Science Study 2019, to answer two research questions. First, which European countries are most likely to have experienced higher learning loss among their children? Second, which European countries have most likely experienced the greatest increases in learning inequalities? Results based on 4th graders’ school achievements indicate that educational inequalities between and within countries are likely to have augmented substantially throughout Europe. Some European countries are probably already facing an education crisis.